The relationship between duration of betel chewing and caries status and oral hygiene status in the Pomako Village community aged 26-35 years: Hubungan lama menyirih terhadap status karies dan status kebersihan gigi mulut pada masyarakat Kampung Pomako usia 26-35 tahun - Sari Aldilawati; Ilmianti; Nur Fadhilah Arifin; Yusrini Selviani; Putri Ananda (Makassar Dental Journal, 2026)
Oral health is an important aspect of a person's general health. This study analyses the relationship between the duration of betel chewing and the status of ca-ries and oral hygiene in the 26-35-year-old population of Kampung Pomako. This quantitative cross-sectional study consisted of individuals who had a habit of chewing betel, and the sample was selected using accidental sampling techniques. Data were collected through interviews, clinical observations, and examina-tions to measure the respondents' caries status and oral hygiene status. It appears that the habit of continuous betel nut chewing and poor oral hygiene tends to increase the risk of plaque formation, tartar, and tooth discolouration. Based on the Spearman correlation test, a p-value of 0.040 (< 0.05) was obtained, which means that there is a significant relationship between the duration of betel nut chewing and dental caries status, but there is no significant relationship bet-ween the duration of betel nut chewing and dental and oral hygiene status (p-value 0.077). It is concluded that education on dental and oral hygiene is import-ant for people who have a betel nut chewing habit.